Racial Differences in Professional Basketball Players' Compensation - Kahn, Lawrence M.; Sherer, Peter D. (Journal of Labor Economics, 1988)
This article investigates racial differences in 1985-86 salaries of individual professional basketball players. White and black players earn similar mean compensation; however, controlling for a variety of productivity and market-related variables and for the endogeneity of player draft position, we find a significant ceteris paribus black compensation shortfall of about 20%. Further, we find that all else equal, including team performance and market factors, replacing one black player with an identical white player raises home attendance by 8,000 to 13,000 fans per season. The compensation and attendance results together are consistent with the idea of customer discrimination.